An integrated view of innate immune mechanisms in C. elegans - Harding, Benjamin W; Ewbank, Jonathan J (Biochemical Society transactions, 2021)
The simple notion 'infection causes an immune response' is being progressively refined as it becomes clear that immune mechanisms cannot be understood in isolation, but need to be considered in a more global context with other cellular and physiological processes. In part, this reflects the deployment by pathogens of virulence factors that target diverse cellular processes, such as translation or mitochondrial respiration, often with great molecular specificity. It also reflects molecular cross-talk between a broad range of host signalling pathways. Studies with the model animal C. elegans have uncovered a range of examples wherein innate immune responses are intimately connected with different homeostatic mechanisms, and can influence reproduction, ageing and neurodegeneration, as well as various other aspects of its biology. Here we provide a short overview of a number of such connections, highlighting recent discoveries that further the construction of a fully integrated view of innate immunity.